Language and Nation. Ethnocultural Aspects of Language Communication - Edens, Dayana (Media and Language, 2021)
In this research the ethnocultural aspects of linguistic communication of two nations are analyzed Bulgarian and English. It is questioned whether the native language is part of the identity and can be a source for pride. Bulgaria and Great Britain face the same problem – the language of hatred(hate speech) and the crimes that follow from it. Different definitions of offensive speech are considered, as well as the main causes of aggression – ethnicity, appearance etc.The relationship between stereotypes and values are also analyzed. Attention is paid to the cultural context and its influence on human relationships. Measures to deal with hate speech are proposed to improve the individual’s communication and understanding of „others“ – „not ours“.